Parents' perspectives on speech-language assessment for their preschool-aged children: A scoping review. - Duggleby Wenzel, Shanda; Pritchard-Wiart, Lesley; Charest, Monique (International Journal of Speech-Language Pathology, 2025)
Purpose: Assessment allows speech-language pathologists to identify clients' strengths and needs while laying the foundation for the therapeutic relationship. However, the extent to which parents' experiences with assessment has been explored in the literature is unclear. The purposes of this review were to: a) Identify and summarise the available literature on parents' experiences with speech-language assessment for their preschool-aged children, and b) identify gaps in the literature. Method: Using an established framework for scoping reviews, the authors conducted a search of seven databases including literature up to April 2024. Two researchers independently reviewed articles for inclusion and discussed discrepancies, and a third researcher provided input when consensus could not be reached. Data extracted included study aims, participant information, and the aspects of the assessment process including the lead-up to the assessment, the assessment itself, receiving a diagnosis, and interim supports following the assessment. Result: Ten studies met inclusion criteria, however, only three studies were focussed on parents' experiences with speech-language assessment. Conclusion: In the included studies, aspects of assessment have been addressed but with limited depth and breadth. To date, the perspectives studied have primarily been those of monolingual, English-speaking mothers. Proposed reporting considerations are discussed, and clinical and research implications are explored.